การวัดสมรรถนะของ โรงพยาบาลเชียงใหม่ราม จำกัด โดยใช้กระบวนการตัดสินใจแบบวิเคราะห์ลำดับชั้น - กฤติญา สุวรรณลิขิต (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study aimed to develop performance measurement model of Chiangmai Ram Hospital Company Limited to be applied with the assessment of overall performance index of the studied company. In this study, five attributes of the performance measures composed of patient safety quality in clinical, patient safety quality in patient care team, management assessment, international patient safety, and patient safety quality program were selected. 25 significant measures were carefully picked from the total of 117 measures, according to the consideration of frequency and the judgment of six hospital administrators. After that, these six hospital administrators applied the analytic hierarchy process for pairwise comparison, as well as the geometric mean for group judgment in order to figure out the relative weight of importance of the measures. Each administrator was requested to determine two-points in each measure to figure out the best conceivable value of the performance (at the score of 10) and the worst conceivable value of the performance (at the score of 0). The arithmetic mean was, then, applied to acquire the best and the worst conceivable performance means. Later, the linear value function of each measure was established to convert performance value of each measure in each month to be ranked in the score of 0-10. The obtained score was multiplied by the value of relative weight of importance of the measure. The sum of 25 measures was, then, calculated to figure out the overall performance index of the Chiangmai Ram Hospital in the following months. According to the interview with the administrators, benefits of this performance measurement model were to foresee the tendency of overall significant performance of Chiangmai Ram Hospital as well as to help verifying and monitoring unusual performance as found in each approach in each month to get to know which measure that caused such an unusual performance and to be able to find solutions, accordingly.